PEMANFAATAN IKAN NILA DALAM PEMBUATAN KULIT PANGSIT DAN ISIAN PRODUK PANGSIT GORENG - Hamidah, Azahra Syafa; Chayati, Ichda (Prosiding Pendidikan Teknik Boga Busana, 2023)
Nille tilapia is a type of freshwater fish that is often found and consumed by Indonesian people. This is because nille tilapia can adapt even in an unfavorable environment. Even so, nille tilapia is a fish with a better protein content than other freshwater fish. In order to increase fish consumption among the younger generation, an innovative product of processed nille tilapia is made, namely fried Nille tilapia dumplings called "Panggori". The purpose of this study was to find a recipe with the right composition and processing technique to determine the level of public acceptance of the Nille tilapia fried dumpling product. The type of research used is R & D (Research and Development) with the 4D method (define, design, develop, and disseminate). Product research was carried out by adding 10% nille tilapia flour to dumpling skin and 100% Nille tilapia meat added to the spicy taste of chili in the dumpling filling. The products were presented and tested by 50 panelists at the culinary product innovation exhibition. The results of the preference test data for 50 panelists found that there were no significant differences in both the reference product and the development product so that the product was acceptable. The values obtained in the preference test starting from color, aroma, taste, texture, packaging, and overall are around an average of 3.96 to 4.58. Thus, the product of fried nille tilapia dumplings can be well received and includes food suitable for consumption.